2015
DOI: 10.3748/wjg.v21.i26.8073
|View full text |Cite
|
Sign up to set email alerts
|

Extrahepatic portacaval shuntviaa magnetic compression technique: A cadaveric feasibility study

Abstract: Author contributions: Yan XP and Liu WY contributed equally to this work; Yan XP and Lv Y designed the study; Yan XP, Lv Y and Ma J performed the research and acquired the data; Yan XP and Li JP analyzed the data; Yan XP, Liu WY and Li JP drafted the manuscript; Yan XP, Liu WY, Ma J and Li JP contributed significantly to the revision of the manuscript. Institutional review board statement: The entire study was carried out in strict accordance with protocols approved by the Xi'an Jiaotong University Biomedical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…In-human trials have demonstrated decreased anastomotic and total procedure times, with no device-related adverse events and favorable patency rates at 6-month follow-ups [ 68 , 70 , 72 , 73 , 74 , 76 , 119 ]. Preclinical animal studies are also being used to explore the use of MCAs in the creation of vascular anastomoses, but these have not progressed to in-human trials at this point [ 120 , 121 , 122 , 123 ].…”
Section: Core Functions Of Magnetic Surgical Devicesmentioning
confidence: 99%
“…In-human trials have demonstrated decreased anastomotic and total procedure times, with no device-related adverse events and favorable patency rates at 6-month follow-ups [ 68 , 70 , 72 , 73 , 74 , 76 , 119 ]. Preclinical animal studies are also being used to explore the use of MCAs in the creation of vascular anastomoses, but these have not progressed to in-human trials at this point [ 120 , 121 , 122 , 123 ].…”
Section: Core Functions Of Magnetic Surgical Devicesmentioning
confidence: 99%
“…Currently, it is a popular new anastomosis method. The MCT exploits the attraction between magnets to pull together an area of ischemic necrosis and its surrounding tissue to promote healing 8 . MCT has been applied in many scenarios, especially in the digestive system, such as esophageal magnamosis 9 , 10 , gastroesophageal magnamosis 11 , gastrojejunal magnamosis 12 , enteric magnamosis 13 , 14 , and choledochojejunostomy magnamosis 15 , 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that magnetic compression is a simple, minimally invasive, and reliable technique for surgical anastomosis[7,8]. Currently, the magnetic com-pression technique (MCT) is applied therapeutically for repair and reconstruction in esophageal atresia[9], biliary stenosis[10-14], vascular anastomosis[15-22], and gastro-intestinal anastomosis[23-30].…”
Section: Introductionmentioning
confidence: 99%